Industrial Controls and Manufacturing. - Kamen, Edward W.
Growing numbers of engineering graduates are finding employment in the control systems area with applications to manufacturing. To be properly prepared for such positions, it is desirable that the students be exposed to the topics of process control, discrete logic control and the fundamentals of manufacturing. Presently there is no existing textbook and/or reference that combine together process control, discrete logic control and the fundamentals of manufacturing. This is a book that fills that gap. This book integrates together the theory with a number of illustrative examples. Constructive.